PF‐04447943, a Phosphodiesterase 9A Inhibitor, in Stable Sickle Cell Disease Patients: A Phase Ib Randomized, Placebo‐Controlled Study. Issue 2 (31st December 2018) - Charnigo, Robert J.; Beidler, David; Rybin, Denis; Pittman, Debra D.; Tan, Beesan; Howard, Jo; Michelson, Alan D.; Frelinger, Andrew L.; Clarke, Nicholas
Abstract : This phase Ib study randomized patients with stable sickle cell disease (SCD) aged 18–65 years to twice‐daily PF‐04447943 (a phosphodiesterase 9A inhibitor; 5 or 25 mg) or placebo, with/without hydroxyurea coadministration, for up to 29 days. Blood samples were collected at baseline and various posttreatment time points for assessments of PF‐04447943 pharmacokinetics (PKs)/pharmacodynamics (PDs). Change from baseline in potential SCD‐related biomarkers was evaluated. Of 30 patients, 15 received hydroxyurea and 28 completed the study. PF‐04447943, with/without hydroxyurea, was generally well tolerated, with no treatment‐related serious adverse events. Plasma PF‐04447943 exposure was dose proportional. Twice‐daily PF‐04447943 25 mg significantly reduced the number and size of circulating monocyte‐platelet and neutrophil‐platelet aggregates and levels of circulating soluble E‐selectin at day 29 vs. baseline (adjusted P  < 0.15). PF‐04447943 demonstrated PK/PD effects suggestive of inhibiting pathways that may contribute to vaso‐occlusion. This study also provides guidance regarding biomarkers for future SCD studies.